2022
DOI: 10.1177/03057356221109328
|View full text |Cite
|
Sign up to set email alerts
|

A PRISMA review of research on feedback in music education and music psychology

Abstract: The purpose of this study was to conduct a systematic review of research literature about feedback in music. We employed the Preferred Reporting Systems for Systematic Reviews and Meta-Analyses (PRISMA) method to systematically review literature about feedback in music education and music psychology from the first identified article in 1973 to November 2021. We identified a total of 4,499 records using our inclusion criteria, of which a total of 153 were identified as relevant for further analysis. We document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…While it is not particularly surprising that any skill would be developed through practice, feedback has been an under-researched skill, suggesting that it has not been seen as a high priority item in previous research or in music teacher education (Blackwell et al, 2022; McPherson et al, 2022). It seems that feedback has been treated as implicitly important, without meaningful investigation into how, when, or why to give feedback, or even what constitutes meaningful feedback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is not particularly surprising that any skill would be developed through practice, feedback has been an under-researched skill, suggesting that it has not been seen as a high priority item in previous research or in music teacher education (Blackwell et al, 2022; McPherson et al, 2022). It seems that feedback has been treated as implicitly important, without meaningful investigation into how, when, or why to give feedback, or even what constitutes meaningful feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Teachout, 1997). Identifying the limitations of past research on feedback in music, Blackwell and colleagues (2022) suggested a framework for how feedback could be incorporated into the process of learning music. To build on this framework, studies identifying effective feedback practices in music education are essential to understand how to effectively use feedback in music contexts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In musical training, students receive feedback and subsequently evaluate their performance against it. This process of reflecting on one’s performance through feedback, identifying areas for improvement, strengthens learners’ abilities for self-monitoring and evaluation ( Fritz et al, 2020 , Tang et al, 2022 ; Blackwell et al, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, immediate feedback occurs within individual practice sessions where, upon completing a section, teachers or recording software provide instantaneous evaluations and suggestions. Finally, delayed feedback pertains to the provision of feedback after students’ completion of a comprehensive performance or practice session, wherein teachers or peers subsequently provide summary evaluations ( Wu et al, 2020 ; Blackwell et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%